Experiences With Base Grouted Drilled Shafts In The Southeastern United States - Steven D. Dapp (Deep Foundations Institute, 2006)
The use of base grouting (tip grouting) to enhance the axial capacity of drilled shaft foundations can achieve improvements in economy and reliability for many types of projects and soil profiles. Recent experiences on a range of different construction projects in the Southeastern U.S. illustrate the most attractive opportunities for utilizing this technique and some limitations of the method. The quality assurance provided by measurements obtained during post grouting the pile toe is another important aspect favoring its use; the base grouting is shown to identify weaker piles and provide a means of remediating some deficiencies so that increased foundation reliability is achieved. This paper provides an overview of the methods used to evaluate and design for base grouted shafts along with lessons learned from several case histories.